The product range conceptualization for Islamic SME financing - Ahmad Aizuddin Hamzah; Norhazlina Ibrahim; Amir Shaharuddin; Sumaiyah Abd Aziz; Haneffa Muchlis Gazali (Penerbit UMS, 2021)
The SME sector is the most critical client for bank financing, particularly in commercial business banking. A dual banking system in which Islamic and conventional financial institutions coexist makes the financial market more competitive. To ensure that Islamic financial products and services can compete with the existing market, Islamic banking management must ensure that its services, particularly in the SME sector, have a place. Knowing the banking product preferences of those firms is one of the steps that should be taken. As a result, this study will develop a conceptual framework for the product range of Islamic banking products to investigate the SME owner's preference for Islamic SME financing. The product range of this range will be strengthened further with the theoretical support of planned behavior from the Managerial perspective among SMEs.